PENINGKATAN KEMAMPUAN MENYANYIKAN LAGU WAJIB DENGAN MENGGUNAKAN METODE DEMONSTRASI - Asnida, Rita; Mansurdin, Mansurdin; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstrack The purpose of this research is to describe the improvement of the singing anthem skill using demonstration method in Grade IV of Elementary School 10, Ulakan Tapakis. This research is a Class Action Research which uses qualitative and quantitative approach with 16 people, teacher and Grade VI students, as the research subjects. The research results show the performance process and the singing skill of the students is improved. Based on the data analysis, it is obtained: the plan result on cycle I is by 73.5% in average and is improved on cycle II by 93%, the teacher’s performance on Cycle I is by 72% in average and is improved on cycle II by 89%, the students’ performance result on cycle I is by 74% in average and is improved on cycle II by 87%, the students’ learning result on cycle I is by 67.2% in average and is is improved on cycle II by 83.3%. Keywords: the singing anthem skill, demonstration